2007
DOI: 10.1192/bjp.bp.106.028647
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antidepressant treatment following myocardial infarction

Abstract: BackgroundDepression following myocardial infarction is associated with poor cardiac prognosis. It is unclear whether antidepressant treatment improves long-term depression status and cardiac prognosis.AimsTo evaluate the effects of antidepressant treatment compared with usual care in an effectiveness study.MethodIn a multicentre randomised controlled trial, 2177 myocardial infarction patients were evaluated for ICD–10 depression and randomised to intervention (n=209) or care as usual (n=122). Both arms were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
188
0
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 291 publications
(199 citation statements)
references
References 34 publications
4
188
0
7
Order By: Relevance
“…Finally, it is possible that the differential prognostic effects of the cutoff scores ≥2 versus ≥3 on the PHQ-2 may be attributed to anti-depressant therapy being more prevalent in patients with the higher cutoff. However, this explanation seems unlikely, given evidence from large-scale trials in cardiac patients 37,38 , showing that antidepressant therapy may reduce depression but not enhance survival. Similarly, it is possible that differences in cardiac medication between the two cutoffs would be responsible for their differential prognostic effects.…”
Section: Discussionmentioning
confidence: 96%
“…Finally, it is possible that the differential prognostic effects of the cutoff scores ≥2 versus ≥3 on the PHQ-2 may be attributed to anti-depressant therapy being more prevalent in patients with the higher cutoff. However, this explanation seems unlikely, given evidence from large-scale trials in cardiac patients 37,38 , showing that antidepressant therapy may reduce depression but not enhance survival. Similarly, it is possible that differences in cardiac medication between the two cutoffs would be responsible for their differential prognostic effects.…”
Section: Discussionmentioning
confidence: 96%
“…As for now, randomized controlled trials in CVD-free populations have not yet been carried out. Some trials (SADHART, (Glassman et al 2002); ENRICHD, (Berkman et al 2003); MIND-IT, (van Melle et al 2007)) did investigate the effects of antidepressant psychotherapy or pharmacotherapy on cardiovascular morbidity and mortality in coronary patient populations. Although these studies have shown that depression is treatable in coronary patients, no significant differences were found in medical end-points between intervention and control groups.…”
Section: Possible Implicationsmentioning
confidence: 99%
“…Those with elevated depressive symptoms had 25-34% increased risk of deaths per standard deviation increase in depressive symptoms. However, despite the fact that depressive symptoms seem to confer increased mortality risk, the treatment of depression has failed to show any alleviation of risk (The ENRICHD Investigators, 2003; van Melle et al, 2007), thereby calling into question whether depression can truly be seen as a risk factor for MI, or is better seen as a risk marker (Freedland and Carney, 2013;Meijer et al, 2013b). …”
Section: Introductionmentioning
confidence: 99%